Patient Satisfaction with Services in King Abdulaziz University Dental Hospital - Ghada H. Naguib; Mohamed T. Hamed; Abeer M. Alnowaiser; Amal M. Sindi; Nadia Al-Hazmi (Journal of King Abdulaziz University: Medical Sciences, 2023)
Patient satisfaction levels in any health institute are a key performance indicator of quality health care. We constructed a 36-item questionnaire and distributed it over a three-month period (from February to April 2014) to 301 patients treated in various departmental clinics at King Abdulaziz University Dental Hospital. The survey addressed satisfaction with facilities, helpfulness of the staff, progress of treatment, quality of care and treatment with dignity and compassion. Patients were overall satisfied with the treatment received (84.1%), with particular satisfaction for doctors and faculty supervisors being courteous (73.4%, and 61.0%, respectively), and addressing their concern (54.3% and 60.0%, respectively). Dissatisfaction was found with the patient relations’ attitude (48.2%) and professionalism (49.6%), and the majority of patients claimed to be very unsatisfied with the referral system (69.0%) and the difficulty in contacting the clinics (72.0%). The results of the present study revealed that King Abdulaziz University Dental Hospital provides quality dental services to its patients and there is an overall high rate of patient satisfaction for the treatment and services rendered by the institute. However there are still issues and some concerns such as patient relation communication skills and referral system professionalism that have to be addressed in order to improve the patient experience.